“IMPORTANCE OF LESSON PLANNING SKILLS IN EFL TEACHING” - Mamadjanova Maftuna Uktamovna; Shumqoraliyeva Shahloxon Azizbek qizi (Ta’lim innovatsiyasi va integratsiyasi, 2023)
Abstract: Lesson planning is a crucial aspect of effective English as a Foreign Language (EFL) teaching. This article explores the significance of lesson planning skills in EFL instruction, highlighting the benefits of well-structured and thoughtfully designed lessons for student learning outcomes. By examining the impact of lesson planning on language acquisition, student engagement, and classroom management, this article aims to underscore the importance of lesson planning skills in EFL teaching.